The use of social media in personal marketing: a study on the strategic positioning of personalities participating in the Big Brother Brasil 2021 (Research, Society and Development, 2022)
Reality shows have a great reach in Brazil. They are able to promote significant financial returns and generate an expressive audience of telespectateurs. As a consequence of the massifying reach of realities, the personalities competing in it have their images exposed to the Brazilian public in an unmeasurable way. The objective of this essay is to study how the reality shows can favor the fortification of the participants’ personal image throughout Digital Marketing aiming to turn the participants into valuable brands for business. It is purposed to analyse case studies to identify the used strategy on social media, the public reaction to the participant positioning and the gains quantification in terms of followers and partnerships. It was learned that the participants’ personal image is favored when social media are strategically used, building a strong relationship with a fan network and reinforcing the solid identification of the participant during and after the reality show. When well used, Digital Marketing can create a loyal public to the participant and, so, turn him/her into a valuable brand for business.